2013
DOI: 10.3109/09638288.2013.829527
|View full text |Cite
|
Sign up to set email alerts
|

Muscle load in reaching movements performed by a wheelchair user: a case study

Abstract: Handling heavy objects such as a pack of bottles or a wheelchair produces high forces on the rotator cuff muscles and can lead to early fatigue. Therefore, these activities seem to be associated with a high risk of developing impingement syndrome. Implications for Rehabilitation In a single patient, this study demonstrates that the load on the rotator cuff is high during reaching movements. Handling a pack of water bottles, which resembles wheelchair handling, represents an activity associated with a high risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The overhead requirements of daily living have received little attention; recent studies, however, have shown that load during overhead movements in wheelchair users was higher than for mere wheelchair propulsion. 18 The daily living activities in wheelchair-dependent individuals involve continuous and repetitive use (overuse) of their rotator cuff muscles, and it seems reasonable to assume that structural changes of the shoulder joint are more frequent, more severe, and probably more disabling in individuals with longstanding paraplegia. The reported prevalence of rotator cuff lesions in the weight-bearing shoulder was 63% after a mean of 33.7 years of wheelchair dependency in a population with a mean age of 52 years, 1 and overall, up to 65% to 73% of wheelchair users with pain have rotator cuff tears.…”
mentioning
confidence: 99%
“…The overhead requirements of daily living have received little attention; recent studies, however, have shown that load during overhead movements in wheelchair users was higher than for mere wheelchair propulsion. 18 The daily living activities in wheelchair-dependent individuals involve continuous and repetitive use (overuse) of their rotator cuff muscles, and it seems reasonable to assume that structural changes of the shoulder joint are more frequent, more severe, and probably more disabling in individuals with longstanding paraplegia. The reported prevalence of rotator cuff lesions in the weight-bearing shoulder was 63% after a mean of 33.7 years of wheelchair dependency in a population with a mean age of 52 years, 1 and overall, up to 65% to 73% of wheelchair users with pain have rotator cuff tears.…”
mentioning
confidence: 99%